2021
DOI: 10.1038/s41598-021-00299-2
|View full text |Cite
|
Sign up to set email alerts
|

Proteomic analysis of peritoneal fluid identified COMP and TGFBI as new candidate biomarkers for endometriosis

Abstract: Endometriosis is a common non-malignant gynecological disease that significantly compromises fertility and quality of life of the majority of patients. The gold standard for diagnosis is visual inspection of the pelvic organs by surgical laparoscopy and there are no biomarkers that would allow non-invasive diagnosis. The pathogenesis of endometriosis is not completely understood, thus analysis of peritoneal fluid might contribute in this respect. Our prospective case–control study included 58 patients undergoi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
22
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(23 citation statements)
references
References 66 publications
1
22
0
Order By: Relevance
“…So far, a number of studies have used this platform to discover novel pathways or biomarker signatures specific for certain diseases [ 32 , 33 , 34 ]. Additionally, we have previously used the same platform to successfully identify biomarker candidates for endometriosis in peritoneal fluid samples [ 26 ].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…So far, a number of studies have used this platform to discover novel pathways or biomarker signatures specific for certain diseases [ 32 , 33 , 34 ]. Additionally, we have previously used the same platform to successfully identify biomarker candidates for endometriosis in peritoneal fluid samples [ 26 ].…”
Section: Discussionmentioning
confidence: 99%
“…Peritoneal fluid is considered a better source for cytokine detection than peripheral blood because immune cells of peritoneal fluid specifically reflect the pathology of endometriosis [ 57 ]. In our previous study, peritoneal fluid was proven to be more appropriate for the discovery of novel biomarkers of endometriosis using antibody array platforms [ 26 ]. We were able to identify 16 differential proteins between control and endometriosis patients and successfully validated three biomarker candidates in a larger cohort.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The D469del-COMP mutant mice show an increase in the adipogenic marker Cebps, possibly contributing to the imbalance between adipogenesis and osteogenesis in mutant mice [ 15 ]. Using proteomic analysis, Janša et al identified that COMP is one of the 16 proteins with different levels in peritoneal fluid of endometriosis patients compared with controls [ 136 ]. Although the cells that secrete COMP are unknown, they reported that COMP could be a potential diagnostic and predictive biomarker of endometriosis [ 136 ].…”
Section: Comp and Other Diseasesmentioning
confidence: 99%
“…Using proteomic analysis, Janša et al identified that COMP is one of the 16 proteins with different levels in peritoneal fluid of endometriosis patients compared with controls [ 136 ]. Although the cells that secrete COMP are unknown, they reported that COMP could be a potential diagnostic and predictive biomarker of endometriosis [ 136 ].…”
Section: Comp and Other Diseasesmentioning
confidence: 99%